Digitalisasi Koperasi Gapoktan Tani Mulus Desa Mundakjaya Kecamatan Cikedung Indramayu - Irwanto Ali Udin; Reyhan Kusuma; Jaja Abdul Jalil; Anita Setianingsih; Gilang Tejawangsa; Wiwiek Rabiatul Adawiyah (Sinergi Abdimas Jurnal Pengabdian Masyarakat, 2024)
Farmer Groups are farmer-owned institutions that grow and develop from, by and for farmers. Thus, farmer groups form from shared interests, environmental, social, economic, cultural, and resource conditions. This community service program (PPM) activity solves problems and helps communities without expecting rewards. Gapoktan Tani Mulus was founded on December 19, 2007, in Mundakjaya Village, Cikedung District, Indramayu Regency. Vision: Building Modern, Environmentally Friendly and Strong Agriculture, Livestock and Fisheries. Mission: Developing and facilitating farmers as well as transforming the latest and sustainable farming techniques. Digital marketing is a marketing activity or promotion of a brand or product using digital media or the internet. This study prioritizes the use of methods that are appropriate to the subject matter of the research being conducted, in order to obtain relevant data for further discussion. This research is intended to obtain an overall picture of the development of Micro, Small and Medium Enterprises (MSMEs) related to digital marketing for the Mulus Farmers Cooperative in Mundakjaya Village. The focus in this research is related to the development of digital marketing for the Mulus Farmers Cooperative in Mundakjaya Village.